Amphetamine Abuse Related Acute Myocardial Infarction. (21st February 2016) - Sinha, Archana; Lewis, O'Dene; Kumar, Rajan; Yeruva, Sri Lakshmi Hyndavi; Curry, Bryan H.
Abstract : Amphetamine abuse is a global problem. The cardiotoxic manifestations like acute myocardial infarction (AMI), heart failure, or arrhythmia related to misuse of amphetamine and its synthetic derivatives have been documented but are rather rare. Amphetamine-related AMI is even rarer. We report two cases of men who came to emergency department (ED) with chest pain, palpitation, or seizure and were subsequently found to have myocardial infarction associated with the use of amphetamines. It is crucial that, with increase in amphetamine abuse, clinicians are aware of this potentially dire complication. Patients with low to intermediate risk for coronary artery disease with atypical presentation may benefit from obtaining detailed substance abuse history and urine drug screen if deemed necessary.